A Robotic Storage Facility for the Dutch National Library Collections. (10th August 2022) - Boersma, Foekje; Martens, Marco; Ankersmit, Bart; Stappers, Marc
ABSTRACT: The KB National Library of the Netherlands (KB) is developing a new offsite storage facility for rehousing its entire physical collection. In an effort to become more sustainable, the national collection will be housed in a purpose-built passive building without elaborate heating, ventilation and air conditioning (HVAC) systems. Using a super high-density automated storage and retrieval system (ASRS), the combination of building and collections plays a major role in establishing a safe climate. Since control over the indoor environment in this new building is limited, it is vital to study the hygrothermal behavior of the building and collection by modelling. This simulation is novel in that it explores the impact of collections on the indoor environment. The effect on the indoor relative humidity (RH) of the way in which the storage volume is progressively filled and of the moisture content of the collection are evaluated.